2012
DOI: 10.1002/jms.2955
|View full text |Cite
|
Sign up to set email alerts
|

Gas‐flow assisted ion transfer for mass spectrometry

Abstract: Methods and devices that use gas flows to collect ions and transfer them over long distances for mass spectrometric analysis have been developed. Gas flows derived from the ionization source itself or provided by means of additional pumping were used to generate a laminar flow inside cylindrical tube. Hydrodynamic simulations and experimental tests demonstrate that laminar flow can transfer ions over long distance. The typical angular discrimination effects encountered when sampling ions from ambient ionizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
58
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 40 publications
2
58
0
Order By: Relevance
“…20,23,28 In this current study, we observed that the types of the materials used for the ion transfer tube had a significant impact on the ion transfer. For an investigation for selection of the transfer tube, six common types of plastic tubes (all 1 m long, 1.6 mm i.d.)…”
Section: Resultsmentioning
confidence: 69%
“…20,23,28 In this current study, we observed that the types of the materials used for the ion transfer tube had a significant impact on the ion transfer. For an investigation for selection of the transfer tube, six common types of plastic tubes (all 1 m long, 1.6 mm i.d.)…”
Section: Resultsmentioning
confidence: 69%
“…As previously reported, appropriate gas ow can assist the ion transfer. 16,17) en, to facilitate the effective uptake of ions into the original ion inlet of the mass spectrometer, it was necessary to attach a bespoke adaptor to an additional diaphragm pump. is modi cation made it possible for the ion sampling ori ce to be placed immediately next to large living animals, which would otherwise be too large to be placed inside the ionization chamber of a conventional MS system.…”
Section: Introductionmentioning
confidence: 99%
“…[40] The flow dynamics in the ion transfer process was also studied. [41] For clinical applications, a rapid evaporative ionization mass spectrometry system (REIMS) system was developed in which tissue was ionized by a surgical knife and the ions subsequently transferred to a mass spectrometer for analysis. [7] A sampling probe using DESI and a narrow (1.6 mm i.d.…”
Section: Introductionmentioning
confidence: 99%
“…[42] Transfer of dry ions generated by atmospheric pressure chemical ionization or by LTP over long distances has been shown to have relatively lower efficiency in comparison with transfer of sprayed ions. [41, 43, 44]…”
Section: Introductionmentioning
confidence: 99%